EDUKASI LITERASI KESEHATAN SEBAGAI UPAYA PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH YANG DILAKSANAKAN DI TPQ AL JADID KARANG GANTING KECAMATAN KURANJI KOTA PADANG - Sidaria Sidaria; Dewi Murni; Muthmainnah Muthmainnah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2022)
The implementation of education in the city of Padang has been carried out online and face-to-face, including at the elementary school level. Face-to-face learning has a high risk of COVID-19 transmission. For this reason, the COVID-19 prevention health protocol is very important that must be implemented by students and schools. From the observations of elementary school students at SD N 21 Lubuk Lintah, Kuranji District, they still do not comply with health protocols such as washing hands, keeping a distance from friends and masks that often hang around their necks. To improve student behavior in implementing health protocols, health literacy can be done. The purpose of this activity is to increase the knowledge of school-age children about the importance of implementing COVID-19 preventive health protocols and implementing COVID-19 prevention health protocols at school and outside the school environment. The activity was carried out at the TPQ of the Al Jadid Mosque, Karang Ganting, Kuranji District because it was not clear when face-to-face learning would be conducted after the online learning was resumed. The activity was carried out with a health literacy approach, namely by providing material about COVID-19 and COVID-19 prevention health protocols to 50 students, demonstrating the implementation of health protocols and motivating students to apply health protocols. The activity continued with the delivery of masks, hand sanitizers, hand soap to the Head of the TPQ of the Al Jadid mosque and attaching posters on how to wash hands and posters of health protocols. The results of the evaluation showed that there was an increase in the behavior of implementing the protocol during the pre-test and post-test. Suggestions for the school and the TPQ to continue to motivate students to carry out health protocols and monitor the implementation of health protocols.